Influence of sarmata burial customs on changes of soil redox conditions - Fuchs, Márta; Szegi, Tamás; Michéli, Erika (JOURNAL OF LANDSCAPE ECOLOGY, 2006)
Pedology is an important tool in reconstruction of the environments of archeological sites. The 30 ha archeological site of a 4th-5th century sarmata pottery village raised several questions that needed pedological research to be answered. The archaeological site is located in the outskirts of Üllő, in near the junction of M60 motorway and 4th main road. The excavation was started in 2001. The territory of the site is more than 30 hectares now and includes fireplaces, storage pits, cisterns, buildings and three cemeteries, with 10-12 graves. Ditches surrounded most of these graves, and they were probably covered with mounds, which have been destroyed by intensive agricultural activity. Most questions that were related to location of fireplaces and storage pits in the ancient landscape were relatively easy to answer based on preserved genetic horizons of the soil mantel. A confusing formation of iron crusts in well drained, coarse textured, Calcic Chernozem (WRB) soil of the area induced the presented more detailed investigation. Two soil-forming processes can lead to removal and concentration of iron in soils, namely podzolisation and redox processes (oxidation-reduction processes). Podzolisation occurs only in acidic, well-drained sandy soil where organic acid from the litter layer dissolves iron and aluminum hydroxides in the upper part of the soil by forming complexes with the iron and aluminium. These complexes subsequently become mobile and are leached from the top layer by the percolated water and re-precipitate in the subsoil below. The enriched horizons, also called spodic horizons may be firmly cemented by leached and re-precipitated iron and aluminum compounds. Redox processes (oxidation and reduction processes) primarily take place in waterlogged soils. Here the biological activity will quickly consume all the oxygen and soil will become anaerobic. Ferric iron will be reduced to ferrous iron and the soil will lose its brownish color and turn olive, bluish or gray. The ferrous iron, being somewhat more mobile will follow the water movement and re-precipitate as ferric-hydroxides in places more rich in oxygen. Where a sharp and well-defined border between aerobic and anaerobic soil conditions is found, the iron precipitation may take place in a narrow zone and thus develop a hard, dense pan. During our investigations, according to Danish literature and experiences, we’ve proved this iron pan was developed under redox conditions. Based on the analytical data and the soil formation environment of the iron pan, the following hypothesis is suggested for the development of the iron pans. Shortly after construction of the pits and ditches anaerobic conditions arose in the core of the mound as a result of the decomposition of organic material. Soil aeration was impeded because of the distance between the core and the mound surface and the relatively wet and compact conditions in the core of the mound. Probably the core was soaked and treaded down during the erection of the mound to get a better structure, or it was just a chance that caused anaerobic conditions in the centre of the mound. Ferric iron was converted into ferrous and moved from the anaerobic core to more aerobic parts in the mound. At the border between the wet, anaerobic core and the dry aerobic areas, the iron was precipitated as ferric iron creating a thin, strongly cemented iron pan.
Keywords: archaeology; soil science; iron pan; podzolisation; redox processes; human impact